Perspectives on healthcare, chronic non-communicable disease, and healthworlds in an urban and rural setting - Ibanez-Gonzalez, Daniel Lopes (My University, 2014)
BACKGROUND: Amidst diverging discourses describing chronic non-communicable disease (NCD) and healthcare access, the hermeneutical tradition within sociology, particularly as exemplified in the work of Jurgen Habermas, provides a starting point for exploring and interpreting the experiences of chronic illness and healthcare access. In this study, we aimed to understand how women living with NCDs experience their illness and access healthcare in an urban and rural context. METHODS: This study was a mixed-methods comparative case study of the healthcare access experiences of women with NCDs in an urban and rural area in South Africa. The core of the study methodology was a comparative qualitative case study, with quantitative methods serving to contextualise the findings. RESULTS: The cross-sectional survey describes a low resource population with a high prevalence of NCDs. Slightly over half the respondents in urban Soweto (50.7%) reported having at least one NCD. Only around a third (33.3%) of these participants reported accessing formal healthcare services in the past 6 months. Similar trends were found in the review of research carried out in rural Agincourt. The qualitative case study in Soweto is characterised by a preoccupation with how medicine from the clinic interacts with the body. The Agincourt qualitative case study highlights the importance of church membership, particularly of African Christian Churches, as the strongest factor motivating against the open use of traditional medicine. DISCUSSION: A consideration of the findings suggests five broad themes for further research: 1) processes of constructing body narratives; 2) encounters with purposive-rational systems; 3) encounters with traditional medicine; 4) encounters with contemporary informal medicine; and 5) religion and healthcare. These five themes constitute the beginning of a comprehensive schema of the lifeworld/healthworld.
KIM
Keywords: South Africa